The weakest link: Haploid honey bees are more susceptible to neonicotinoid insecticides. (March 2020) - Friedli, Andrea; Williams, Geoffrey R.; Bruckner, Selina; Neumann, Peter; Straub, Lars
Abstract: Neonicotinoid insecticides are currently of major concern for the health of wild and managed insects that provide key ecosystem services like pollination. Even though sublethal effects of neonicotinoids are well known, there is surprisingly little information on how they possibly impact developmental stability, and to what extent genetics are involved. This holds especially true for haploid individuals because they are hemizygous at detoxification loci and may be more susceptible. Here we take advantage of haplodiploidy in Western honey bees, Apis mellifera, to show for the first time that neonicotinoids affect developmental stability in diploid females (workers), and that haploid males (drones) are even more susceptible. Phenotypic fore wing venation abnormalities and fluctuating wing asymmetry, as measures of developmental instability, were significantly increased under field-realistic neonicotinoid-exposure of colonies. The higher susceptibility of haploid drones suggests that heterozygosity can play a key role in the ability to buffer the sublethal effects of neonicotinoids. Aiming to improve conservation efforts, our findings highlight the urgent need to better understand the role that genetics plays at enabling non-target organisms to cope with insecticide exposure. Highlights: Neonicotinoid insecticides affected the developmental stability of honey bees. Haploid males were more susceptible to neonicotinoids than diploid females. Heterozygosity may play a key role in buffering insecticide exposure.